Motivations of volunteering during crises: Perspectives of Polish youths during the Ukrainian refugee crisis - Debashish Sengupta; Aniisu K. Verghese; Maciej Rys (Administrative Sciences, 2023)
Volunteering work has always played a key role in dealing with crises around the world. Understanding the motivations behind volunteering during a crisis could not only explain such behaviour but also become a guide for the government for future policies, to non-governmental organizations for attracting and recruiting more volunteers, for companies to attract and engage young talent and for society to encourage volunteering more. The present military conflict between Russia and Ukraine has resulted in an influx of over six million Ukrainian refugees in Poland. Given the phenomenal response of Polish people towards welcoming the Ukrainian refugees and, in general, the favourable attitude of the youth in Poland towards extending humanitarian aid to them, our present study examines the motivations of Polish youths behind volunteering during crises. The study also examined how volunteering has influenced their lives and future, besides understanding the barriers to volunteering. The research participants were Polish youths aged between 17-30 years of age. The participants were from both genders, students as well as working professionals. To take part, they had to prove that they took an active role in volunteering during a crisis and were able to share their personal stories and emotions in English. The findings of the research revealed normative, hedonic, eudaimonic and personal motivators behind volunteering during crises, with greater dominance of hedonic motivators, followed by normative, then eudaimonic and personal motivators. The influence of a mix of collectivist and individualistic cultures of Poland, with a progressive lean towards individualism, is clear in shaping the motivations behind the volunteering of these Polish youths. The role of intrinsic motivation is more pronounced when it comes to volunteering during crises.
Keywords: 350; motivations; crises; Poland; Ukrainian refugees; volunteering; youth